2007
DOI: 10.1093/carcin/bgm188
|View full text |Cite
|
Sign up to set email alerts
|

Modes of actions of two types of anti-neoplastic drugs, dacarbazine and ACNU, to induce apoptosis

Abstract: O(6)-Methylguanine and O(6)-chloroethylguanine, which are the primary cytotoxic DNA lesions produced by 5-(3,3-dimethyl-1-triazeno)imidazole-4-carboxamide (dacarbazine) and 1-(4-amino-2-methyl-5-pyrimidinyl)methyl-3-(2-chloroethyl)-3-nitrosourea (ACNU), respectively, can be repaired by O(6)-methylguanine-DNA methyltransferase (MGMT), coded by the MGMT gene. However, the two types of drugs exhibit different effects on cells defective in both MGMT and MLH1 functions, the latter being related to the cellular acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…3 and 4). It has been previously reported that DTIC (2 mM) kills cells in a manner related to apoptosis, 22 and our results exhibited that DTIC (5 ug/ml) primarily led to cell arrest in the G 1 phase in UM cell lines. Nevertheless, the differences in action of DTIC may be due to different concentrations used (2 mM vs. 5 mg/ml).…”
Section: Discussionsupporting
confidence: 77%
“…3 and 4). It has been previously reported that DTIC (2 mM) kills cells in a manner related to apoptosis, 22 and our results exhibited that DTIC (5 ug/ml) primarily led to cell arrest in the G 1 phase in UM cell lines. Nevertheless, the differences in action of DTIC may be due to different concentrations used (2 mM vs. 5 mg/ml).…”
Section: Discussionsupporting
confidence: 77%
“…The MutSa, consisting of MSH2 and MSH6, and PCNA complex first recognizes O 6 -meG:T mispair in DNA and then MutLa, composed of MLH1 and PMS2, binds to the initial complex. The formation of the mismatch recognition complex is indispensable for the activation of DNA damage signaling as well as the induction of apoptosis (Hidaka et al, 2005;Yoshioka et al, 2006;Sanada et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A new apoptosis-inducing protein, MAPO1 K Komori et al Sanada et al, 2007). These results imply that KH101 cells might have a defect in a gene involved in the induction of cell death caused by MNU-induced O 6 -methylguanine.…”
Section: Isolation Of Mutant Cells Defective In Omentioning
confidence: 93%
See 2 more Smart Citations